2004
DOI: 10.1038/sj.mp.4001587
|View full text |Cite
|
Sign up to set email alerts
|

Association of a corticotropin-releasing hormone receptor 1 haplotype and antidepressant treatment response in Mexican-Americans

Abstract: There are well-replicated, independent lines of evidence supporting a role for corticotropinreleasing hormone (CRH) in the pathophysiology of depression. CRH receptor 1 (CRHR1), which we first mapped in the brain in 1994, has been implicated in the treatment of depression and anxiety. We studied the association of CRHR1 genotypes with the phenotype of antidepressant treatment response in 80 depressed Mexican-Americans in Los Angeles who completed a prospective randomized, placebo lead-in, double-blind treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
83
4
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(97 citation statements)
references
References 61 publications
7
83
4
2
Order By: Relevance
“…In a pharmacogenetic study in MexicanAmerican outpatients with depression, mean decrease in HDRS was about 30% after 3 weeks of treatment with either fluoxetine or desipramine. 21 In a similar study on the catechol-O-methyltransferase Val/Met polymorphism in patients treated with mirtazapine, patients had a mean decrease in HDRS-17 score of 38% after 3 weeks, 32 which is similar to our results. These comparisons show that our sample is a typical sample of moderately to severely depressed patients.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In a pharmacogenetic study in MexicanAmerican outpatients with depression, mean decrease in HDRS was about 30% after 3 weeks of treatment with either fluoxetine or desipramine. 21 In a similar study on the catechol-O-methyltransferase Val/Met polymorphism in patients treated with mirtazapine, patients had a mean decrease in HDRS-17 score of 38% after 3 weeks, 32 which is similar to our results. These comparisons show that our sample is a typical sample of moderately to severely depressed patients.…”
Section: Discussionsupporting
confidence: 81%
“…As primary parameter of response, reduction in HDRS during 3 weeks of treatment was calculated as (HDRS 1 -HDRS 21 )/ HDRS 1 *100, with HDRS 1 and HDRS 21 being the total score of the 21-item HDRS at day 1 (baseline) and day 21, respectively. 21 Response was defined as a decrease in HDRS of more than 50%, according to the World Federation of Societies of Biological Psychiatry (WFSBP) Guidelines for Biological Treatment of Unipolar Depressive Disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, pharmacogenomic evidence suggests a role for genetic variants in elements of the HPA axis, including the CRH receptor type 1 (CRHR1) in the response to antidepressants. 37,38 Given the abundant data supporting a role for CRH dysregulation in depression, CRH receptor antagonists have been developed as a new strategy for pharmacotherapy of depression. Such drugs have already been tested in clinical trials.…”
Section: Hpa Axis Dysregulation In Obesity and Depressionmentioning
confidence: 99%
“…Surprisingly little is known about influence of genetic variations in the CRHR1 gene in the context of stress and depression, since only a few such studies have been reported up to date (Licinio et al, 2004;Liu et al, 2007;Liu et al, 2006;Papiol et al, 2007;Wasserman et al, 2007). In fact, our group has been the first to study the genetic variation in the CRHR1 gene in connection to depression and stress among suicidal individuals (Wasserman et al, 2007).…”
mentioning
confidence: 99%